Communication in Health Care - Branger, P. J.; Duisterhout, J. S. (Methods of Information in Medicine, 1995)
For routine communication, care providers still mainly rely on paper documents and paper mail. Evidence exists, however, that this communication can be improved, both by a better content of information exchange and by a more timely deliverance of this information. At present, several alternatives to paper-based communication are available, such as the Fax, the Smart Card, electronic mail, and electronic data interchange. This paper describes existing communication problems, and examines the current state of development and research aimed at improving this communication using electronic communication techniques that are gradually replacing paper-based communication. Applicability and shortcomings of these new techniques are also discussed.
Keywords: Communication; Telemedicine; Networking; HL-7; EDI; EDIFACT; PACS